Some Aspects of the Regulatory Environment of Local Self-Government in Federal Cities - O. A. Kozhevnikov; O. I. Beketov (Сибирское юридическое обозрение, 2023)
The issues of legal regulation of the organization and functioning of all government bodi es have always been the subject of numerous studies, discussions and even disputes. The rapid new reorganization of the legal foundations of the unified system of public power that started in 2020, having passed the federal and regional level of state power, "stumbled" at the level of local self-government. The draft federal law No. 40361-8 "On General Principles of Organization of Local Self-Government in the Unified System of Public Power", which was submitted to the State Duma of the Russian Fe deration on 16 December 2021, has so far remained at the level of "proposals and comments for the second reading". This allows us to focus on the analysis of problematic issues of the current situation with the legislative basis of local self-government in Russia in order to avoid and take into account in the future existing errors and shortcomings, as well as to improve the current system of legal regulation of local self-government as soon as possible. The Authors of this study attempt to analyze and draw the attention of other researchers, representatives of federal and regional legislative authorities to the existing obvious problems in the legislative regulation of local self-government in federal cities. Specific examples of the texts of the laws of Moscow, St. Petersburg and Sevastopol, allow us to draw disappointing conclusions about the significant abuse by the legislators of these constituent entities of the Russian Federation of their rights to regulate certain issues of organization and functioning of local self-government in the territory of federal cities. Evidently, the existing conflicts should be eliminated as soon as possible and taken into account by the federal legislator in the formation of future legislative framework for determining the specifics of local self-government in federal cities. The current situation seriously affects the principle of direct and immediate effect of the Constitution of the Russian Federation, as well as the priority of federal legislation over regional legislation on issues of joint jurisdiction of the Russian Federation and its constituent entities.